Systematic literature review: implementation of inclusive education policies in Indonesia: a state administration perspective - Todapa, Daniel T (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study thoroughly investigated the implementation of inclusive education policies in Indonesia, focusing specifically on the state administration perspective. Using a systematic literature review (SLR) approach, the research meticulously identifies meticulously identified the main challenges encountered and proposes proposed effective solutions for policy implementation. The key themes highlighted in this study include the urgent need for improved educational facilities, comprehensive teacher training programs, and the development of flexible teaching methods tailored to the individual needs of each student. Additionally, the findings underscore underscored the critical importance of stakeholder collaboration and the continuous assessment of policies to adequately meet the diverse needs of all students. This comprehensive and in-depth analysis not only contributed to a more inclusive and equitable education system in Indonesia but also provided valuable insights that are essential for future policy enhancements. By addressing these issues in detail, the study aimed to pave the way for more effective and inclusive educational practices across the nation.